Zakah compliance in Muslim countries: an economic and socio-psychological perspective. Issue 3 (7th December 2020) - Bin-Nashwan, Saeed Awadh; Abdul-Jabbar, Hijattulah; Aziz, Saliza Abdul; Sarea, Adel
Abstract : Purpose: Although Zakah is the cornerstone of the social protection system in Muslim societies, providing relief to those in need and collecting funds from those who have access to money and property, many administrative and legal improvements need to be made to ensure that Zakah funds are managed effectively and efficiently in Muslim states. It is therefore important to recognize why some Muslims are not paying their Zakah through Zakah authorities. The purpose of this paper is to propose a viable and comprehensive research model, derived from an economic and socio-psychological perspective, to provide a richer understanding of Zakah payers' compliance behaviour. Design/methodology/approach: Drawing on extant literature, this study offers a conceptual framework for a better understanding of compliance behaviour by proposing an economic and socio-psychological model based on Fischer's tax compliance model, which could be applied cautiously in an Islamic setting like Zakah. Findings: The four main categories of the Fischer model are derived from socio-psychological and economic perspectives, namely, attitude and perception (system fairness, ethics and peer influence); Zakah system structure (Zakah law complexity and law enforcement); non-compliance opportunity (education level, wealth source and occupation); and demographic factors (age and gender). Each has much to offer in understanding Zakah payers' compliance decisions. To suit the nature of Zakah, the influence of Islamic religiosity and the moderating effect of trust in the Zakah institution are incorporated into the model. Practical implications: Those Muslim communities that strive to have functional Zakah systems to search for solutions to the perennial problem of low Zakah funding and its damning consequences, are offered a compliance model for systematically assessing Muslims' compliance behaviour with Zakah provisions. This framework is anticipated to offer invaluable input to policymakers in streaming and strategizing the minimization of losses of Zakah revenue to Zakah authorities. Originality/value: Although behavioural models such as the theory of reasoned action and the theory of planned behaviour have been extensively used in Zakah compliance studies, to the best of the authors' knowledge, this study is perhaps the first to apply a socio-psychological and economic framework, emerging from tax literature, in the Zakah environment to develop fully understanding of Zakah payers' compliance decisions.